2014
DOI: 10.1021/la5012296
|View full text |Cite
|
Sign up to set email alerts
|

Role of Subcolloidal (Nanosized) Precursor Species in the Early Stage of the Crystallization of Zeolites in Heterogeneous Systems

Abstract: A critical analysis was carried out for the purpose of understanding the role of subcolloidal (nanosized) (alumino)silicate precursor species in the early stage of crystallization of zeolites in heterogeneous systems (hydrogels). The formation and evolution of these subcolloidal species in both the solid and the liquid phases were investigated by various experimental methods such a scanning electron microscopy (SEM, FE-SEM), transmission electron microscopy, atomic force microscopy, particle size analysis, pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…For these reasons, great attempts were made to elucidate the "structure" and properties of the sub-colloidal particles and their role in zeolite crystallization. 5,6,11,[23][24][25][27][28][29][30][31][32][34][35][36][37][38][39][40][41][42][43][44][45][46] On the basis of numerous studies of the formation of silica nanoparticles in homogeneous systems TEOS-TAAOH-H 2 O, 27,34,[47][48][49][50] it was concluded that silica-TAAOH solutions have well defined critical aggregation concentration (CAC) of silica for OH -/SiO 2 = TAAOH/TEOS ≈ 1. Many studies 21,27,30,34,[47][48][49][50] suggest that prior to this critical point (below the CAC; OH -/SiO 2 > 1) the solution (HmRM) contains only silicate monomers and polysilicate anions (oligomers).…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, great attempts were made to elucidate the "structure" and properties of the sub-colloidal particles and their role in zeolite crystallization. 5,6,11,[23][24][25][27][28][29][30][31][32][34][35][36][37][38][39][40][41][42][43][44][45][46] On the basis of numerous studies of the formation of silica nanoparticles in homogeneous systems TEOS-TAAOH-H 2 O, 27,34,[47][48][49][50] it was concluded that silica-TAAOH solutions have well defined critical aggregation concentration (CAC) of silica for OH -/SiO 2 = TAAOH/TEOS ≈ 1. Many studies 21,27,30,34,[47][48][49][50] suggest that prior to this critical point (below the CAC; OH -/SiO 2 > 1) the solution (HmRM) contains only silicate monomers and polysilicate anions (oligomers).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the SEM images indicate a classical homogeneous nucleation mechanism, in which nucleation of zeolite crystals are originated from the solution phase and occur at the boundary of the amorphous solid gel and the surrounding solution [21]. Again, this excluded the particle attachment mechanism that has been frequently observed in the crystallization of MFI zeolites [29][30][31]. The structure evolution was further monitored after the full crystallization of ZSM-5 plates at 120 h. A minor diffraction peak, possibly ascribe to MOR, appeared at 168 h and remarkably intensified at 240 h. Meanwhile, the plate surface became rough and the straight edges (and angels) nearly disappeared at 168 h. The intergrowth architecture destructed seriously and some plates were broken at 240 h, together with a small amount of thin plates.…”
Section: Resultsmentioning
confidence: 89%
“…The chemical shift at 54 ppm in 27 Al MAS NMR spectrum was ascribed to tetrahedrally coordinated framework Al species (95.4%) [37], while the chemical shift at 0 ppm represented the extra-framework Al species (4.6%) that might be generated during the calcination and ion-exchange processes. Si(0Al) at -113 ppm and Si(1Al) at -107 ppm were identified from 29 Si MAS NMR. Accordingly, the framework SiO2/Al2O3 ratio was estimated to be 37.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the formation of WLPs in gels resulting in ZSM-5 was proposed to stem from the aggregation of primary particles of approximately 3 nm as well as the coalescence and disaggregation of different intermediates, with aluminum-containing precursor species playing a major role in the aggregation process [18]. However, no clear inhomogeneity or internal structure could be directly evidenced within the WLPs or gel aggregates in these two studies.…”
Section: Introductionmentioning
confidence: 80%